From the Planned Space to the Inhabited Place: Processes of Appropriation and Territorial Reconfigurations in Social High-Rise Housing Complex (Ciudadela Nuevo Usme, Bogotá) - Dérégnieaux, Luc (Universidad del Rosario, 2022)
In the southern outskirts of Bogotá, the Ciudadela Nuevo Usme is characteristic of a new social housing offering built since the mid-2000s by the private sector. This article seeks to give an account of the experience lived by the residents of this emerging model of vertical social habitat. Our study is based on field work done in 2018 in two closed residential complexes in the Ciudadela, aimed at low-income populations and displaced households, victims of the armed conflict. Through a study of of living patterns and focusing on the divergences between the constructed space and the inhabited space, we will try to evaluate the adequacy of this housing offer to the needs and aspirations of its beneficiaries. To this end, we will carry out a multiscale analysis of the “practices of places” and representations of space of the inhabitants of these apartment blocks.